Differences in work values and organizational commitment by generation and gender-a study in an accounting firm - Chen Hui, Ching (Universiti Malaysia Sarawak, (UNIMAS), 2019)
This study intended to identify the differences in work values and organizational commitment by generation and gender in an accounting firm. The research method used in this study was quantitative approach through survey questionnaire. The data was analyzed using the Statistics Package for Social Science (SPSS) 22.0. 68 employees were participated in this research as the sample. Generational differences in work values and organizational commitment was analysed with One-way ANOVA while insignificant gender differences in work values was shown through Independent Sample T-Test. The positive relationship between work values and job commitment was examined with Pearson Correlation Analysis. Hierarchical Regression Analysis was used in examining the moderating effect of generation and gender in the relationship between work values and job commitment. Generation was showing partial moderating effect while weak moderating effect were shown on gender. The findings indicated that human resource practitioners and organization should take generational and gender differences into consideration upon creating person job fit environment which increase the organizational commitment. In order to have further insights related to this topic, future researchers are recommended to include other demographic factors and conduct in a different setting of culture and profession.